PARADIGMA BARU PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Mohamad Ahyar Ma’arif (Nurul Jadid University, 2018)
National education is education based on Pancasila and Law that is rooted in the values of religion, culture of the Indonesian nation. sustainability and national and institutional education objectives are directed to form a healthy human body and spirit, internalize faith and devotion, have knowledge and skills, be able to develop creativity and responsibility, able to develop high intelligence with noble character and loves nation and neighbor human. To get to the expected educational objectives the curriculum has a very urgent position as a guide for determining the direction of content and educational goals. Therefore, curriculum development in the field of Islamic Religious Education becomes part of the educational strategy in shaping the character of learners who are martyred against the development, growth and development of the whole person.